Impact of Antibiotics and Proton Pump Inhibitors on Efficacy and Tolerance of Anti-PD-1 Immune Checkpoint Inhibitors - Giordan, Quentin; Salleron, Julia; Vallance, Catherine; Moriana, Clothilde; Clement-Duchene, Christelle (Frontiers in Immunology, 2021)
Background: The use of antibiotics (ATB) and proton-pump inhibitors (PPI) alters the composition and diversity of the gut microbiota, which can influence the immune system, consequently interfering with response to anti-PD1 immune checkpoint inhibitors (ICI). We assessed the impact of ATB and/or PPI use on the efficacy and safety of ICI. Methods: Two hundred twelve patients treated with anti-PD1 ICI for non-small cell lung carcinoma, melanoma, upper airway & digestive tract carcinoma or renal cell carcinoma were retrospectively included. Patients having received ATB within 60 days before ICI initiation were included in the ATB+ group. Patients having received PPI within 30 days before ICI initiation were included in the PPI+ group. Four groups were thus considered: ATB-/PPI-, ATB+/PPI-, ATB-/PPI+, ATB+/PPI+. Response rate was assessed by RECIST v1.1. Overall survival (OS), progression-free survival (PFS) and adverse events, recorded using Common Terminology Criteria for Adverse Events Version 5, were compared using inverse probability of treatment weighting to account for selection bias. Results: PFS at 6 months was 56.7 %, 95%CI [49.6%; 63.2%] and 47.2 %, 95%CI [39.8%;54.1%] at 12 months. OS was 81.6%, 95%CI [75.6%; 86.2%] at 6 months, and 69.4%, 95%CI [61.9%;75.7%] at 12 months. Compared to ATB-/PPI- group, PFS was lower for the ATB+/PPI- group (Hazard ratio (HR) 1.90, 95%CI [1.41;2.57]) and the ATB-/PPI+ group (HR 1.51, 95%CI [1.11;2.05]), and lowest in the ATB+/PPI+ group (HR 3.65, 95%CI [2.75;4.84]). For OS, the use of ATB alone or PPI alone or in combination was a risk factor for death, with each increasing HR values by a similar magnitude, and the combination of ATB and PPI did not increase risk further. AEs were observed in 78 cases (36.8 %) with no significant impact of ATB or PPI use. Conclusions: This study reveals that ATB and/or PPI use can alter response to anti-PD1 ICI, and the prognosis of cancer patients. The microbiota mechanisms involved in the response to ICI should be investigated to optimize patient management.